Comparison of Silicon MOSFET, Silicon Carbide MOSFET and Gallium Nitride MOSFET in EV Charging Application. - Lim, Kee Han; Razali, Muhammad Anas (Evolution in Electrical and Electronic Engineering, 2024)
This research focuses on the comparison of Silicon MOSFET, Silicon Carbide (SiC) MOSFET, and Gallium Nitride (GaN) MOSFET in electric vehicle (EV) charging applications. The study evaluates the performance, efficiency, and overall feasibility of these semiconductor devices in the context of their implementation in EV charging systems. Using simulation models developed in MATLAB/Simulink, the study evaluates the efficiency, power losses, and overall performance of inverters containing these semiconductor devices. The results showed that SiC and GaN MOSFETs offer superior performance over traditional Si MOSFETs in terms of efficiency which is critical for high-frequency operations in EV charging systems. The findings suggest that adopting SiC and GaN technologies can lead to more efficient and reliable EV charging solutions, highlighting their potential to enhance the future landscape of EV infrastructure.